Real-World Problems for Secondary School Mathematics Students Case Studies - Maasz, Juergen; O$1 (BDonoghue, John.s; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
This is a book full of ideas for introducing real world problems into mathematics classrooms and assisting teachers and students to benefit from the experience. Taken as a whole these contributions provide a rich resource for mathematics teachers and their students that is readily available in a single volume. Nowadays there is a universal emphasis on teaching for understanding, motivating students to learn mathematics and using real world problems to improve the mathematics experience of school students. However, using real world problems in mathematics classrooms places extra demands on teachers in terms of extra-mathematical knowledge e.g. knowledge of the area of applications, and pedagogical knowledge. Care must also be taken to avoid overly complex situations and applications. Papers in this collection offer a practical perspective on these issues, and more. While many papers offer specific well worked out lesson type ideas, others concentrate on the teacher knowledge needed to introduce real world applications of mathematics into the classroom. We are confident that mathematics teachers who read the book will find a myriad of ways to introduce the material into their classrooms whether in ways suggested by the contributing authors or in their own ways, perhaps through mini-projects or extended projects or practical sessions or enquiry based learning. We are happy if they do! This book is written for mathematics classroom teachers and their students, mathematics teacher educators, and mathematics teachers in training at pre-service and in-service phases of their careers.
Keywords: Education; Mathematics; Education; Mathematics Education